2017
DOI: 10.18203/2394-6040.ijcmph20171460
|View full text |Cite
|
Sign up to set email alerts
|

Study of biomedical waste management among healthcare personnel at a Tertiary hospital in Lucknow district

Abstract: INTRODUCTIONDemand of healthcare need has increased drastically over the last few decades and simultaneously the number of healthcare facilities has increased in order to cater to the demands and needs of the people. There by increasing the quantum of hospital waste production. According to WHO, of the total amount of waste generated by healthcare activities, about 85% is general, non-hazardous waste and the remaining 15% is considered hazardous material that may be infectious, toxic or radioactive. Although, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
6
2
Order By: Relevance
“…However, very few of these participants were aware that sharps should be disposed of when the container is three quarters full. These findings were higher than those of a study conducted at a tertiary hospital at Lucknow district, whereby only 66% of the health professionals reported to know the correct waste container for sharps waste disposal [ 31 ]. On average, about half of the Northern Cape tertiary hospital participants were aware of the bin for anatomical waste disposal and the bin for pharmaceutical waste, but very few managed to identify the bin for cytotoxic waste.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, very few of these participants were aware that sharps should be disposed of when the container is three quarters full. These findings were higher than those of a study conducted at a tertiary hospital at Lucknow district, whereby only 66% of the health professionals reported to know the correct waste container for sharps waste disposal [ 31 ]. On average, about half of the Northern Cape tertiary hospital participants were aware of the bin for anatomical waste disposal and the bin for pharmaceutical waste, but very few managed to identify the bin for cytotoxic waste.…”
Section: Discussionmentioning
confidence: 62%
“…This result suggests that experienced professionals were more knowledgeable on the period for which HCRW are stored before disposal, whereas gender may have the upper hand on cumulative knowledge on waste storage period. The results of a similar study conducted among post-graduates, doctors, nurses, laboratory technicians and domestic workers in Lucknow district showed that there was association between waste segregation practices and age, gender, occupation status, work experience and training and it was statistically significant ( p < 0.05) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only 40% of the nurses had adequate knowledge of color-coding which was also improved after training. In another study, the same results showed a significant association between waste segregation and training of BWM among HCWs [ 16 ]. Therefore, training is an effective method that can make an appreciable increase in the knowledge about the color coding of biomedical waste.…”
Section: Discussionmentioning
confidence: 70%
“…The awareness of color coding is very important for the nurses because segregation at the point of generation in specified color containers was done by biomedical waste handlers [ 12 , 16 ]. All nurses should know about the waste and specific color where it can be collected from the wards and operation theaters [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 Deress 9 Imchen et al found total of 78% health care personnel had received training on BMW management. 10 Most of the doctors (76.2%), staff nurses (70.6%) and laboratory technicians (72.2%) had received hepatitis B vaccination and injection TT, 76.2% doctors, 85.9% staff nurses and 69.4% laboratory technicians had received it. Multivariate logistic regression showed association between waste segregation practices and occupation status and training which was statistically significant.…”
Section: Discussionmentioning
confidence: 99%